Characterization of silicon quantum dots synthesized via hydrothermal method and its application for glucose detection - Abdullah, Jaafar; Yusof, Nor Azah; Hassan, Grema; Mohd Chaculi, Siti Haziyah (Universiti Kebangsaan Malaysia Press, 2024)
Recent interest has been directed towards developing new nanomaterials with diverse properties. Among these, silicon quantum dots (SiQDs) have gained popularity in biological applications due to their excellent biocompatibility and optical features. This study describes the synthesis of fluorescence water-soluble silicon quantum dots using a one-pot hydrothermal process specifically for glucose detection. The synthesis involved reacting 3-aminopropyltriethoxysilane (APTES) as a precursor, with ethylenediamine as a capping agent and sodium citrate as a reducing agent. The optical features of the SiQDs, including their absorption and emission characteristics, were investigated using UV-Vis and fluorescence spectroscopy. The measurements displayed an absorption pattern from 200 to 400 nm with a prominent shoulder at 329 nm and a maximum emission peak at 382 nm with an excitation of 305 nm. The structural characteristics of the synthesized SiQDs were examined using FTIR. It was found that surface functionalization and bonding composition exhibited strong absorbance at 1101 cm−1 and 1001 cm−1 due to the Si–O bending vibrations. This observation confirms the successful preparation of SiQDs. TEM analysis revealed a surface morphology characterized by a uniform, near-spherical shape, with sizes ranging from 11.81 nm to 12.95 nm. The XRD analysis indicates the amorphous nature of the SiQDs. Subsequently, the performance of the SiQDs in glucose detection was evaluated, revealing linearity in the range of 0.1 to 0.8 mg/ml with a regression equation of y = 20249x - 1682.4 (R2 = 0.9804) and limit of detection (LOD) of 0.03 mg/mL. The findings suggest promising prospects for utilizing SiQDs as sensitive and reliable probes for glucose-sensing applications.